Endophthalmitis after pars plana vitrectomy: Results of the pan American collaborative retina study group (2011)
Purpose: To determine the incidence of endophthalmitis after 20-, 23-, and 25-gauge pars plana vitrectomies (PPVs). Methods: Retrospective comparative case series of consecutive patients who underwent 20-, 23-, or 25-gauge PPV at 11 centers from Latin America between 2005 to 2009. Pars plana vitrectomy cases were identified through a search of the billing records of each institution. Cases of PPV performed in the management of trauma, endophthalmitis, and combined PPV phacoemulsification cases were excluded. Endophthalmitis was diagnosed by clinical criteria regardless of the microbiologic results. The incidence of post-PPV endophthalmitis was compared between 20-, 23-, and 25-gauge PPVs. Results: A total of 35,427 cases of PPV were identified during the study period (n = 19,865 for 20 gauge, n = 10,845 for 23 gauge, and n = 4,717 for 25 gauge). The 5-year post-PPV endophthalmitis incidence rates were 0.020% (4 of 19,865), 0.028% (3 of 10,845), and 0.021% (1 of 4,717) for 20 gauge, 23 gauge, and 25 gauge, respectively (P = 0.9685). Conclusion: Small-gauge transconjunctival PPV does not appear to increase the rates of post-PPV endophthalmitis. © The Ophthalmic Communications Society, Inc.